Development of decision support system prototype for PLKN selection process (DSSPSP) / Masrul Farihan Mohamad - Mohamad, Masrul Farihan (2006)
Decision Support System Prototype for PLKN Selection Process is to assist the risk in selecting an appropriate trainee for PLKN program. This research focuses on selecting all youth aged 18 in the year according to the criteria that stated by government. Several criteria are identified and define; 1) Criteria for each camp, 2) Criteria based on gender at each camp, 3) Criteria for school selection, 4) Criteria based on school activities (merit). The criteria are represented in form of rules to make sure all the information is qualified. The inference engine works by selecting rules for testing and then checking if the condition for that rules are true and match with the condition provided. The multidimensional arrays are used in to represent certain rules. In completing this research, system development life cycle and system requirement engineering process technique are follows. The decision support system helps in making effective and reliable decisions to select the appropriate candidates. The result of this research is the list of qualified or eligible candidates for every series of PLKN in selection year. As a conclusion, this prototype achieved the objectives and succeeds in doing their task for selection candidates for Program Latihan Khidmat Negara.